Effect of fermentation time on the molecular weight distribution of ACE inhibitory peptide from jack bean tempe - Puspitojati, E. (Institute of Physics, 2023)
This research examined the variation in concentration of protein derived from jack bean throughout mold fermentation and the distribution of the molecular weight (MW) of the resultant peptides. In addition, the effects of peptide size on ACE inhibitory action were investigated. The jack bean was soaked and boiled before fermentation, then inoculated using 0.2 of commercial tempe inoculum. Furthermore, the inoculated seeds were incubated at room temperature for 48 h (T48), and 72 h (T72), and unfermented jack bean (T0) was used as a control. The total protein, soluble protein, MW distribution of peptides, and ACE inhibitory action were all examined. The results demonstrated that the concentration of soluble proteins rose as fermentation duration increased (p < 0.05). Meanwhile, the total crude protein in all samples did not change significantly (p > 0.05). The resultant peptides were then separated by dialysis to generate four peptide fractions, namely; fractions A (MW of <1 kDa), B (MW of 1-3.5 kDa), C (MW of 3.5-14 kDa), and D (MW of > 14 kDa). The peptide fractions of the three samples demonstrated that the number of peptides in fraction D decreased significantly during the fermentation, followed by an increase in peptide fractions with smaller MW (Fractions A, B, and C). The number of peptides in fraction A of T0, T48, and T72 was 9.51; 49.87; and 56.31, respectively. The more significant amount of smaller peptides indicated a higher possibility to have the capacity to inhibit ACE. Fractions A, B, C, and D of T72 exhibited ACE inhibitory action with the value of 83.21; 62.53; 61.07; and 49.64, respectively. In this investigation, the ACE inhibitory action was stronger as the MW of the peptides decreased. Fraction A had the greatest inhibitory action with an IC50 of 0.60 mg/mL. In conclusion, the fermentation duration enhanced the concentration of soluble protein. Consequently, jack bean protein degraded into various sizes of peptides during fermentation. Furthermore, the smallest size of peptides fraction demonstrated the best ACE inhibitory activity. A@ Published under licence by IOP Publishing Ltd.